HLA-DRB1, -DQA1 and -DQB1 genotyping of 180 Czech individuals from the Czech Republic pop 3 - Zajacova, Marta; Kotrbova-Kozak, Anna; Cerna, Marie (Human immunology, 2016)
One hundred and eighty Czech individuals from the Czech Republic pop 3 were genotyped at the HLA-DRB1, -DQA1 and -DQB1 loci using sequence-specific primers PCR methods. HLA-DRB1, -DQA1 and -DQB1 genotypes are consistent with expected Hardy-Weinberg (HW) proportions. These genotype data are available in the Allele Frequencies Net Database under identifier AFND.
Keywords: alely; haplotypy; Humans; populační genetika; HLA-DQ alpha-Chains; Czech population; HLA-DRB1 řetězec; HLA-DQ beta-Chains; Genetics, Population; HLA-DQ alfa řetězec; frekvence genu; Haplotypes; Alleles; Genotype; lidé; HLA-DRB1 Chains; HLA alleles; DQA1; HLA-DQ beta řetězec; Czech Republic; Gene Frequency; genotyp; DQB1; Česká republika; DRB1